Seroepidemiologic Survey of Brucellosis Diagnosis Using Agglutination Test Procedures in Cattle Owners and Cattle of Babol - GH Maliji; M Yusef Asna Ashari; AA Sefidgar; MR Yusefi (Tehran University of Medical Sciences, 2007)
Background: The geographic conditions is such that animal husbandry is in separable part of villagers and farmers life and they are at risk of infection due to contact with cattle and on the other hand, the whole peopele urban or rural are using unpaseurized dairy products expose at the risk all of society. Brucellosis diagnosis can have special significance based on serologic tests. The tube Standard test has the most usage in brucellosis diagnosis. Antibodies such as IgM and IgG induce agglotination and in some cases become negative due to to existance of blocking and incomplete antibodies that if so, the above antibodies are detectable through coombs wright test. Methods: In this research, 150 cattle owners and 300 cattle were investigated random during year of 83-84. After blood sampling in view of Rosbangal, tube wright test, 2 ME and Coombs wright test were investigated. Results: Between 150 serum Sample of studing cattle owners, 80 and 70 people were men and women respectively. The relative average of these people was 38.86. The most percent of negative cases dedicated to Rosbangal test is 66.7%. The significant difference wasn't observed with Rosbangal method according to Sex in cattle owners (P value= 0/863). According to the obtained results, the serum titre of tube wright test in the studied people was different from 1/20 to 1/2560 and in (3.3%), (2%) and (0.7%) was 1/640, 1/1280 and 1/2560 respectively. The serum titre 2 ME in (2.7%), (2.7%) and (2%) was 1/160, 1/320 and 1/640 respectively. The serum titre of coombs wright in (8.7%) and (5.3%) was 1/320 and 1/640 respectively. With the above studied, in 300 cattle there was positive 9% with Rosbangal test and serum titre of tube wright (0.7%) 1/160, (0.7%) 1/320, (0.7%) 1/640, (1.3%) 1/1280 and 2 ME serum titre (0.7%) 1/160, (0.3%) 1/320, (1.7%) The major findings of this investigation, the significant agreement statistically between Rosebangal results and the other methods including tube wright, 2 ME and brucella and coombs wright have been observeol in the anti brucella antibody in cattle owners serum (r= 0.667). Conclusion: The fining of this research indicated that Brucellosis is still part of common diseases in the studied region. The Training necessity of transmission routes, effects, preventation methods and environment health control and Veterinary is necessary to reduce this disease.